A semi purified hydroalcoholic fraction from Caesalpinia bonduc seeds causes ergosterol biosynthesis inhibition in Candida albicans resulting in cell membrane damage - Sasidharan, Shan; Nishanth, Kumar S.; Nair, Hareendran. J (Frontiers in Pharmacology, 2023)
Candida species are currently developing resistance to prevailing commercially available drugs, which raises an instantaneous need to discover novel antifungals. To cope with this shocking situation, phytochemicals are the richest, safest, and most potent source of excellent antimicrobials with broad-spectrum activity. The aim of the current study is to explore the anticandidal potential of the various fractions purified from the hydroalcoholic extract of C. bonduc seed. Out of five fractions purified from the hydroalcoholic extract, fraction 3 (Fr. 3) recorded the best activity against C. albicans (8 μg/mL) and thus this species was chosen for further mechanism of action studies. The phytochemical examination reveals that Fr. 3 was found to contain steroids and triterpenoids. This was further supported by LC-QTOF-MS and GCMS analyses. Our findings show that Fr. 3 targets the ergosterol biosynthesis pathway in C. albicans by inhibiting the lanosterol 14-α demethylase enzyme and downregulating expression of its related gene ERG11. Molecular docking outcomes disclosed favorable structural dynamics of the compounds, implying that the compounds present in Fr. 3 would be able to successfully bind to the lanosterol 14-α demethylase, as evidenced by the docked compounds’ strong interaction with the target enzyme’s amino acid residues. Considering virulence factors, the Fr. 3 recorded significant antibiofilm activity as well as germ-tube reduction potential. Furthermore, Fr. 3 enhances the production of intracellular reactive oxygen species (ROS). This suggests that the antifungal activity of Fr. 3 was associated with membrane damage and the induction of ROS production, resulting in cell death. Fluorescence microscopic analysis of PI stained Candida further showed changes in the plasma membrane permeability, which causes severe loss of intracellular material and osmotic balance. This was demonstrated by the potassium ion leakage and release of genetic materials. Finally, the erythrocyte lysis assay confirmed the low cytotoxicity of Fr. 3. Both in silico and in vitro results suggest that Fr. 3 has the potential to propel forward novel antifungal drug discovery programmes.